(untitled) (Albayan Scientific Journal, 2023)
This research studies the migration of Andalusians towards the Middle Maghreb during the seventh A.H/thirteenth A.D century, and highlights its causes and stages, and sheds light on the contributions of Andalusian scientists and their participation in revitalizing the scientific life in its metropolises. Andalusia was living in a state of turmoil and political decline that played a role in the fall of most of the Andalusian cities to the hands of Christians and cast a shadow on economic and social conditions. As a result, many of the inhabitants of Andalusia were forced to migrate towards the Middle Maghreb, where they contributed to the civilization prosperity in various fields, especially the cultural field due to the migration of many intellectuals and senior Andalusian scientists who specialized in various sciences, whether portability or mentality.